Pengaruh Strategi Take And Give dalam Pembelajaran Tematik Terpadu Terhadap Keterampilan Berpikir Kritis Siswa - Maielfi, Dini; Saputri, Lidya (LP2M Universitas Adzkia, 2023)
This research is based on the low critical thinking of students due to the conventional teaching and learning process of teachers. Students have not been able to develop new knowledge actively, students have not been able to think critically in the learning process, students have not been faced with situations that cause conflict in students' minds, students have not been faced with problem solving during the learning process. This study aims to determine the effect of the take and give strategy on students' critical thinking in integrated thematic learning in class V UPT SDN 08 Inderapura Pancung Soal. The population of this study were students of class V UPT SDN 08 Inderapura Pancung Question where class A as an experimental class used a take and give strategy and class B as a control class using conventional learning, with a posttest only control design research design. The data collection in this study was using a critical thinking test in the form of a description of 9 items, the data obtained were analyzed using the t test. Based on the results of this study, it can be seen that t_count = 4.93020 and t_table = 1.70562 and the significant level is 5%. Based on the test t_count>t_(table )( 4.93020> 1.70562) then the hypothesis or H1 is accepted. From the results of the study, it is proven that the take and give strategy has a significant influence on students' critical thinking in integrated thematic learning in class V UPT SDN 08 Inderapura Pancung Soal for the 2021/2022 school year.